2019
DOI: 10.1007/s12639-019-01099-2
|View full text |Cite
|
Sign up to set email alerts
|

New prevalence surveillance of Toxoplasma gondii among rodents and stray cats by ELISA avidity and nested PCR methods, Northeast of Iran

Abstract: Rodents and stray cats are the sources of many parasitic infections including T. gondii, for other animals and human. Toxoplasmosis has a wide range of laboratory factors in its intermediate and definite hosts. Regarding the importance of rodents and stray cats as the hosts that spread the Toxoplasma gondii, it is necessary to obtain comprehensive information about these animals in the life cycle of T. gondii. The objective was to investigate the new prevalence of toxoplasmosis among target animals in Iran, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Molecular detection of GRA 6 gene in some of the seropositive rodents and seronegative cats confirms the T. gondii infection. The results reflecting fewer molecular confirmations of T. gondii infections in seropositive rodents and cat samples are in line with those obtained in study conducted in Iran (Bahadori et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Molecular detection of GRA 6 gene in some of the seropositive rodents and seronegative cats confirms the T. gondii infection. The results reflecting fewer molecular confirmations of T. gondii infections in seropositive rodents and cat samples are in line with those obtained in study conducted in Iran (Bahadori et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…The infection is wide spread, although at varying proportions. For instance, (Bahadori et al, 2019;Ahmad et al, 2012;Gryzbek et al, 2021) in Iran, Pakistan and Poland respectively reported higher seroprevalence while Mgode et al, (2014), Defeo et al, (2002) and Brouat et al, (2018) in Morogoro, Rhode Island and Senegal respectively registered lower seroprevalence rates. The observed variations in seroprevalence rates in different areas could be a function of variations in climatic and ecological properties such as humidity, soil topography, ambient temperature and exposure to ultraviolet rays in the studied areas.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The B1 gene is primarily used for the identification of T. gondii with this type of PCR (Botein et al, 2019;Nakashima et al, 2020;Ngui et al, 2020). However, the Me49, GRA6, and Rep529 genes have also been used as targets (Mousavi et al, 2016;Bahadori et al, 2019;Shahbazi et al, 2019). It is noteworthy that both the B1 and REP 529 genes of T. gondii show more sensitivity and specificity in nested PCR than conventional PCR (Jones et al, 2000;Fallahi et al, 2014b).…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%